(3QSGdI aj GdYOds - (3CHh YHO Gddg eMeO Hf YHO GdcQje Hf eMeO GdeYjdjs
(3ChdgG (B:s
(3CeG HYO habc Gddg ddJbhi GdHGH GdKGfi ajeG jLH Ydi GdCejQ ef MSf GdgjFI s
(3BNQgG (B:s
(3QHfG Efc ef JONd GdfGQ abO CNRjJg heG ddXGdejf ef CfUGQ hdG JNRfG jhe GdbjGeI Efc dG JNda GdejYGO GfJgi eG hLO hSdGe Ydi GdCfHjGA hGdeQSdjf hBNQ OYhfG Cf GdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdNRGfI GdYGeI HGdQHGW (B_ (3GdeZQH (B(364D) s
Keywords: (3GdeLGejYs